y = -1 + 3/8x
2x - 5y = 6
Substitute the first equation into the second equation, since y is already by itself.
2x - 5(-1 + 3/8x) = 6
2x + 5 - 15/8x = 6
2x - 15/8x = 1
16/8x - 15/8x = 1
1/8x = 1 Multiply 8 on both sides to get x by itself
x = 8
Plug x into either of the equations.
y = -1 + 3/8(8)
y = -1 + 3
y = 2
2(8) - 5y = 6
16 - 5y = 6
-5y = -10
y = 2
(8,2)
Answer:
Biconditional statements do not use the key words 'if' and 'then. ' Biconditional statements are true statements that combine the hypothesis and the conclusion with the key words 'if and only if. ' For example, the statement will take this form: (hypothesis) if and only if (conclusion).
Step-by-step explanation:
Answer:
70
Step-by-step explanation:
Graph it
Answer:
Well if you are trying to find the length of each side you Divide 24 by 4 so your answer would be 6
Step-by-step explanation:
Answer:
the answer is 7
Step-by-step explanation:
Add the same term to both sides of the equation
-x=7x-56
−x=7x−56
−x−7x=7x−56−7x